2021
DOI: 10.1371/journal.pgen.1009624
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae’s mysterious Seventh Pandemic island (VSP-II) encodes novel Zur-regulated zinc starvation genes involved in chemotaxis and cell congregation

Abstract: Vibrio cholerae is the causative agent of cholera, a notorious diarrheal disease that is typically transmitted via contaminated drinking water. The current pandemic agent, the El Tor biotype, has undergone several genetic changes that include horizontal acquisition of two genomic islands (VSP-I and VSP-II). VSP presence strongly correlates with pandemicity; however, the contribution of these islands to V. cholerae’s life cycle, particularly the 26-kb VSP-II, remains poorly understood. VSP-II-encoded genes are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 121 publications
(157 reference statements)
0
12
0
1
Order By: Relevance
“…For years only the island’s integrase and cognate recombination directionality factor were known [ 13 ]. It was recently discovered that a gene cluster in VSP-II ( vc0513-0515 ) is a part of the zinc-dependent Zur regulon [ 22 ]. Specifically, vc0513 encodes a transcriptional activator VerA to activate expression of vc0512 ( aerB) to alter chemotaxis and aggregation in an oxygen dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…For years only the island’s integrase and cognate recombination directionality factor were known [ 13 ]. It was recently discovered that a gene cluster in VSP-II ( vc0513-0515 ) is a part of the zinc-dependent Zur regulon [ 22 ]. Specifically, vc0513 encodes a transcriptional activator VerA to activate expression of vc0512 ( aerB) to alter chemotaxis and aggregation in an oxygen dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen sensing may also drive a chemotactic response in V . cholerae through aerotactic chemoreceptors Aer1 [ 55 ] and Aer2 [ 56 ], however this oxygen response pathway is unlikely to be required in vivo as non-chemotactic V . cholerae nevertheless colonize the infant mouse intestine [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomics studies identified two genomic islands, VSP-I and VSP-II, characteristic of strains of the 7PET lineage [11,28]. The genes of these islands are thought to be involved in bacteriophage resistance and bacterial chemotaxis [31,32].…”
Section: Two Pandemic V Cholerae O1 Lineagesmentioning
confidence: 99%
“…Par génomique comparative, il a été possible d'identifier deux îlots génomiques, VSP-I et VSP-II, caractéristiques des souches de la lignée 7PET [11,28]. Des gènes de ces îlots auraient un rôle dans la résistance aux bactériophages et dans le chimiotactisme bactérien [31,32].…”
Section: Deux Lignées Pandémiques De V Cholerae O1unclassified